2015
DOI: 10.1155/2015/387090
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Pathways Associated with Skeletal Muscle Changes after Spinal Cord Injury and Treadmill Locomotor Training

Abstract: The genetic and molecular events associated with changes in muscle mass and function after SCI and after the implementation of candidate therapeutic approaches are still not completely known. The overall objective of this study was to identify key molecular pathways activated with muscle remodeling after SCI and locomotor training. We implemented treadmill training in a well-characterized rat model of moderate SCI and performed genome wide expression profiling on soleus muscles at multiple time points: 3, 8, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…As evidence, after spinal transection, the incorporation of BWSTT completely preserved the muscle mass:body mass ratio [ 195 , 196 ] and prevented ~55% of soleus fCSA loss [ 196 ]. Similarly, in a moderate-contusion SCI model, BWSTT produced 23% higher soleus fCSA and 38% higher soleus peak tetanic force in comparison with untrained SCI animals [ 197 ], with analogous effects reported by others [ 49 , 197 , 198 , 199 , 200 ]. Similarly, several case-report and cohort-studies have reported muscle responses in individuals with motor-incomplete SCI.…”
Section: Activity-based Physical Rehabilitation After Scisupporting
confidence: 59%
See 4 more Smart Citations
“…As evidence, after spinal transection, the incorporation of BWSTT completely preserved the muscle mass:body mass ratio [ 195 , 196 ] and prevented ~55% of soleus fCSA loss [ 196 ]. Similarly, in a moderate-contusion SCI model, BWSTT produced 23% higher soleus fCSA and 38% higher soleus peak tetanic force in comparison with untrained SCI animals [ 197 ], with analogous effects reported by others [ 49 , 197 , 198 , 199 , 200 ]. Similarly, several case-report and cohort-studies have reported muscle responses in individuals with motor-incomplete SCI.…”
Section: Activity-based Physical Rehabilitation After Scisupporting
confidence: 59%
“…The influence of these ubiquitin ligases on skeletal muscle atrophy has been demonstrated by the viral overexpression of MAFbx, which reduced the myotube diameter by ~85% in vitro, and by genetic elimination of MAFbx or MuRF1, which attenuated muscle atrophy in response to sciatic nerve transection [ 48 ]. Within several days of SCI, >50 protein ubiquination pathway genes are upregulated in sublesional muscle [ 49 ], an effect that likely influences the rapid muscle atrophy in response to injury. In particular, MAFbx and MuRF1 mRNA expressions are increased five- to >40-fold within two to eight days of injury [ 50 , 51 , 52 , 53 , 54 ], with protein expressions elevated >two-fold prior to the initiation of muscle atrophy [ 55 ].…”
Section: Neuromuscular Adaptations After Scimentioning
confidence: 99%
See 3 more Smart Citations